Cultural And Physiological Characterization Of Beauveria Bassiana (Journal of Plant Disease Sciences, 2021)
Effect of different media, temperature, humidity and pH were assessed on the basis of radial growth of Beauveria bassiana (NGP-Bb4). SDAY medium (44.00 mm) supported highest mycelia growth of isolate followed by SDA (43.33 mm). The abundant sporulation and maximum radial growth 42.00 mm was recorded at temperature 25°C. The moderate sporulation and least radial growth 28.00 mm was at temperature 35°C. At 95% relative humidity, highest radial growth of 41.66 mm was recorded till 10th day of incubation with abundant sporulation. Data in respect of pH effect revealed that the highest radial growth of 42.67 mm was achieved after 10th days at pH of 6.0 with abundant sporulation. It can be concluded that, SDA medium and temperature 25°C, pH 6.0 and humidity 95 per cent were considered as optimum for growth and sporulation of B. bassiana.
Keywords: Beauveria bassiana; Growth; Humidity; pH; Media; Temperature